The Relationship between Farmers’ Cognitive Flexibility and Adoption of the Improved Cassava Processing Technology - Joshua, Joel Matiku; Massawe, Fatihiya Ally; Mwakalapuka, Amani Angumbwike (International Journal of Asian Social Science, 2020)
Low acceptance to adoption of the innovated farming technologies has been reported elsewhere as a problem deserving investigation. Addressing low acceptance to adoption, the study resulting in this paper examined the relationship between farmers’ cognitive flexibility and adoption of improved cassava processing technology. About 360 participants including 181 (50.3%) males and 178 (49.7%) females were purposively selected from Mara, Mwanza and Kagera regions in Tanzania. Participants responded to questions on cognitive flexibility and adoption of improved cassava processing technology. Other variables such as sex, age, education level, attendance to training, intention to adopt cassava processing technology and participation in other economic activities were also included in the questionnaire. Binary logistic regression analysis indicated that cognitive flexibility alongside attendance to training on improved cassava processing technology and intention to adopt the technology predicted adoption. The paper concludes that cognitive flexibility partly explains adoption of improved cassava processing technology. It further discusses the implications for both practice and future research and further recommends training to farmers that involve developing cognitive flexibility tendencies for adoption of technologies in this ever changing world with diverse and progressive innovations.